Law and literature - Dolin, Kieran (Cambridge : Cambridge University Press, 2017)
Law and Literature presents an authoritative, fresh and accessible new overview of the many ways in which law and literature interact. Written by a team of international experts, it provides a multi-focused history of literary studies' critical interest in ideas of law and justice. It examines the effects of law on writers and their work, ranging from classical tragedy to comics, and from East Africa to Elizabethan England. Over twenty chapters, contributors reveal the intricate and multivalent historical interactions between law and literature, both past and present, and trace the intellectual genesis of the concept of law in literary studies, focusing on major developments in the history of the interdisciplinary project of law and literature, as well as the changing ideas of law, and the cultural contests in which it has figured. Law and Literature will appeal to graduates and scholars working on the intersection between law and literature and in key related areas such as literature and human rights.
Title from publisher's bibliographic system (viewed on 19 Jan 2018).
Keywords: Law and literature